1999
DOI: 10.1017/s0022215100146031
|View full text |Cite
|
Sign up to set email alerts
|

Electrode complications in 100 adults with multichannel cochlear implants

Abstract: At switch-on (first post-operative stimulation of the implant) and during subsequent reprogramming, electrodes can, in some patients, be found to be non-functional or to be performing sub-optimally for a number of reasons. This paper examines the reasons for the poor performance of these electrodes by means of a retrospective analysis of 100 patient records. All of these patients received the Nucleus multichannel device.The most common reason for an electrode to require de-activation was found to be facial ner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
2
8
0
Order By: Relevance
“…Finally, an important goal in fitting a cochlear implant is to get rid of electrodes that produce undesirable stimulations. The complications include stimulation of other facial nerves and muscles, such as vibration, pain, eye twitching, and vestibular responses (Niparko et al , 1991; Stoddart and Cooper, 1999). Occasionally, these complications can be avoided by adjusting the electric stimulation parameters such as the pulse duration and the electrode mode.…”
Section: Engineering Issuesmentioning
confidence: 99%
“…Finally, an important goal in fitting a cochlear implant is to get rid of electrodes that produce undesirable stimulations. The complications include stimulation of other facial nerves and muscles, such as vibration, pain, eye twitching, and vestibular responses (Niparko et al , 1991; Stoddart and Cooper, 1999). Occasionally, these complications can be avoided by adjusting the electric stimulation parameters such as the pulse duration and the electrode mode.…”
Section: Engineering Issuesmentioning
confidence: 99%
“…Still, some patients develop facial nerve stimulation in the absence of any of these conditions. In their review of 100 adult patients receiving cochlear implants, Stoddart et al found that the most common reason for an electrode to require deactivation was facial nerve stimulation 1 …”
Section: Introductionmentioning
confidence: 99%
“…Functioning electrodes may have to be switched off because of inadvertent facial nerve stimulation, especially by the more apical electrodes. 6,7 All these problems can contribute to poor performance in a noisy background and to unsatisfactory performance in single‐word testing in implanted individuals. 1 Further, because cochlear implants require an intact cochlea for implantation, they are not well suited for subjects with malformed cochlea (eg, common cavity or Mondini malformation).…”
Section: Introductionmentioning
confidence: 99%